2001
DOI: 10.1111/j.1747-5457.2001.tb00659.x
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Strike‐slip Faulting in the Basement of the Zagros Fold and Thrust Belt

Abstract: Lateral ofsets in the pattern of seismicity along the Zagros fold and thrust belt indicate that transverse faults segmenting the Arabian basement are active deep-seated strike-slip faults. The dominant NW-SE trending features ofthe belt have undergone repeated horizontal displacements along these transverse faults. These reactivated basement faults, which are inherited from the Pan-African construction phase, controlled both deposition of the Phanerozoic cover before Tertiary-Recent deformation of the Zagros a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
137
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(143 citation statements)
references
References 45 publications
3
137
2
1
Order By: Relevance
“…It has previously been suggested that the Balarud Line represents a region of strike-slip faulting (e.g. Berberian 1995;Hessami et al 2001). However, in agreement with Talebian & Jackson (2004) we find that the earthquakes in this region represent thrust-faulting, so it seems unlikely that the Balarud Line represents a region of active strike-slip faulting.…”
Section: Depth Of Slip and Sedimentary Stratigraphysupporting
confidence: 71%
“…It has previously been suggested that the Balarud Line represents a region of strike-slip faulting (e.g. Berberian 1995;Hessami et al 2001). However, in agreement with Talebian & Jackson (2004) we find that the earthquakes in this region represent thrust-faulting, so it seems unlikely that the Balarud Line represents a region of active strike-slip faulting.…”
Section: Depth Of Slip and Sedimentary Stratigraphysupporting
confidence: 71%
“…These results are consistent with several proposals (Flinch and Casas, 1996;Pohn, 2001;Japas et al, 2010;Oriolo, 2012;Oriolo et al, 2013) where cross-strike structures are described as pre-existing crustal fabrics. Moreover, similar geometrical and kinematical relationships between dextral shear zones and secondary oblique sinistral ones were presented by theoretical models of Jiang (1994) and examples from the Zagros fold and thrust belt (Hessami et al, 2001), the Atacama fault system (Cembrano et al, 2005) and the Cap de Creus (Carreras et al, 2013). However, oblique ENE-trending structures do develop even though previous structures are not present (Fig.…”
Section: Deformation Patternsmentioning
confidence: 99%
“…Moderate to large earthquakes frequently occur but rarely exceed M W = 7.0. Recently determined focal depths (8-14 km) imply that moderate to large earthquakes occur in the uppermost part of the Arabian basement (Ni and Barzangi 1986;Baker et al 1993;Hessami et al 2001;Hatzfeld et al 2010). Focal mechanism solutions (Fig.…”
Section: Zagros Fold-thrust Beltmentioning
confidence: 99%